Response of Indonesia's Foreign Exchange Reserves as a Result of Changes in Exports, Imports, Rupiah/USD Exchange Rate, and External Debt for the First Quarter of 2008-Fourth Quarter of 2021 - Yohan, Yohan; Sir, Samuel Yulius; Cicilia, Vera Sri Endah (Journal Of Accounting Management Business And International Research, 2023)
Foreign exchange reserves are an important indicator for a country in conducting international trade, as well as a benchmark against the strong weak economic fundamentals of a country. This study aims to: 1) Analyze the response of changes in Indonesia's foreign exchange reserves simultaneously as a result of changes in exports, imports, Rupiah/U$D exchange rates, and external debt for the first quarter of 2008 - fourth quarter of 2021, 2) Analyze the response of changes in Indonesia's foreign exchange reserves individually as a result of changes in exports, imports, Rupiah/U$D exchange rates, and external debt for the first quarter of 2008-fourth quarter of 2021. The methods used are autoregressive conditional heteroscedasticity (ARCH) and generalized autoregressive conditional heteroscedasticity (GARCH). The results of the study based on estimates with the GARCH model (1.1) show that together the variables of exports, imports, rupiah exchange rates, and foreign debt have a significant effect on reserves Indonesian foreign exchange. The results of the estimation with the GARCH model (1.1) can be concluded that the export variable has a positive and significant effect on Indonesia's foreign exchange reserves. Import variables have a negative and significant effect on Indonesia's foreign exchange reserves. The rupiah exchange rate variable has a negative and significant effect on Indonesia's foreign exchange reserves, and the external debt variable has a positive and significant effect on the reserve variable. This research is still limited to the variables that are used as the basis for the research model, therefore it is necessary to consider information from the variable measurement of the number of Indonesian workers working abroad at various income levels, so that it can be known the role of Indonesian workers working abroad in increasing foreign exchange reserves.